2007
DOI: 10.1007/s00101-007-1201-1
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacain zur Spinalanästhesie bei der Sectio caesarea

Abstract: Levobupivacaine 7.5 mg did not provide satisfactory intraoperative analgesia in all parturients. There were no statistically significant differences between 10 and 12.5 mg levobupivacaine with respect to analgesic, sensory and motor block characteristics. Therefore, based on these data, 10 mg levobupivacaine is recommended for parturients undergoing elective caesarean section with spinal anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Bremerich et al found that, compared with 7.5 mg of levobupivacaine, 10 and 12.5 mg of levobupivacaine prolonged the duration of effective analgesia postoperatively (45 vs. 81 and 96 min, respectively). [11] These authors recommended 10 mg of levobupivacaine for patients undergoing elective cesarean delivery with spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Bremerich et al found that, compared with 7.5 mg of levobupivacaine, 10 and 12.5 mg of levobupivacaine prolonged the duration of effective analgesia postoperatively (45 vs. 81 and 96 min, respectively). [11] These authors recommended 10 mg of levobupivacaine for patients undergoing elective cesarean delivery with spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…found that, compared to 7.5 mg levobupivacaine, 10 and 12.5 mg levobupivacaine prolonged the duration of effective analgesia postoperatively (45 vs. 81 and 96 min, respectively). [6] These authors recommended 10 mg levobupivacaine for parturients undergoing elective cesarean section with spinal anesthesia. In our study, the dose used was similar.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of local anesthetics administered (10 mg) was chosen in accordance with a recent dose-finding study. [6] Neither the anesthesiologist nor the parturient herself was aware of the drugs or dose administered. Randomization of the parturients was performed with sealed envelope technique, in which each treatment allocation was sealed in an individual envelope, and all sixty envelopes were shuffled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Morris et al studied the impedance cardiography values either during normal pregnancy and postpartum after vaginal or cesarean delivery [ 3 ], while Tihtonen used ICG during the course of caesarian section in pre-eclamptic parturients [ 2 ]. However, to our knowledge, no data are available on impedance measurement during spinal anesthesia with different local anesthetic doses whereas several studies were focused on the optimal dose of local anesthetics to obtain a good anesthesia and reduce the motor block [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%